Assessment of Nurses’ Knowledge Concerning Early Detection for Hypothyroidism/Hyperthyroidism in Baghdad Teaching Hospitals - Ahmed F. Hassan1 , Sabah A. Ahmed2 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Abstract: Hypothyroidism and Hyperthyroidism is the most common endocrine disorders in clinicalpractice. Critical illness is often associated with dysfunctions of thyroid hormone. Thyroid dysfunction is aserious matter if managed inaccurately; it early detection may decrease morbidity and mortality. Objectives:Assessment of nurses’ knowledge concerning early detection for hypothyroidism/hyperthyroidism inBaghdad Teaching Hospitals and to find out a relationship between nurses knowledge with some variablessuch as (age , gender, educational level, and marital statues ).Methodology: A descriptive study wasconducted in the period of December 20th 2019 up to the end of 28th May 2020. The sample consisted of (50)nurses who were systematically selected one by one. The data collected was analyzed using SPSS version22.0. Results: The majority of the study were female who accounted for (72%) of the total participantswhile male constituted (28%). Most of the study participants (34%) were ages 26-30 years old. (44%) ofthe nurses were diploma graduate. Fifty percent of the nurses were married. More than half (58%) of nurseshad experience years in nursing and (80%) of nurses had training course in hospitals, (66%) have numberof training were 1-5 course and (80%) had location of courses in Iraq. Conclusions: Findings of studydemonstrate that, nurses have good knowledge about early detection of Hypothyroidism/Hyperthyroidism.